2013
DOI: 10.1371/journal.ppat.1003298
|View full text |Cite|
|
Sign up to set email alerts
|

Systems Analysis of a RIG-I Agonist Inducing Broad Spectrum Inhibition of Virus Infectivity

Abstract: The RIG-I like receptor pathway is stimulated during RNA virus infection by interaction between cytosolic RIG-I and viral RNA structures that contain short hairpin dsRNA and 5′ triphosphate (5′ppp) terminal structure. In the present study, an RNA agonist of RIG-I was synthesized in vitro and shown to stimulate RIG-I-dependent antiviral responses at concentrations in the picomolar range. In human lung epithelial A549 cells, 5′pppRNA specifically stimulated multiple parameters of the innate antiviral response, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
144
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 87 publications
4
144
0
Order By: Relevance
“…The panhandle structures of most negativestrand RNA viruses are only partially complementary (5,47). Very limited data obtained with authentic viral sequences, such as those of rabies virus and vesicular stomatitis virus, led to the conclusion that RIG-I tolerates partial complementarity in initiating the IFN response (5,48). Indeed, we have demonstrated that the partially complementary IAV panhandle structure is able to bind to and activate RIG-I.…”
Section: Resultsmentioning
confidence: 88%
“…The panhandle structures of most negativestrand RNA viruses are only partially complementary (5,47). Very limited data obtained with authentic viral sequences, such as those of rabies virus and vesicular stomatitis virus, led to the conclusion that RIG-I tolerates partial complementarity in initiating the IFN response (5,48). Indeed, we have demonstrated that the partially complementary IAV panhandle structure is able to bind to and activate RIG-I.…”
Section: Resultsmentioning
confidence: 88%
“…35,36 Conceivably, at lower concentrations of RIG-I in the resting state, RIG-I surveys and binds only the ends of 5′trisphor-phylated RNA, but upon IFN induction and the concomitant increase in cellular levels of RIG-I protein, RIG-I molecules may start to bind internally near the RIG-I-capped RNA. 35,37 A distinct conformation of RIG-I bound internally to the duplex RNA is therefore highly desirable, which may provide a second-similar but not identical-means to activate RIG-I. Carefully designed experiments are needed to further clarify the functional implications of this RNA end capping preference vs. the duplex internal binding activity of RIG-I in vivo.…”
Section: Rig-i Prefers Capping the Ends Of Rna Duplex Rather Than Binmentioning
confidence: 99%
“…We note that KIN1400 treatment induced little if any expression of IFN-␤, type III IFN (IFN-2/3), or the proinflammatory cytokine interleukin-6 (IL-6) compared to the level of expression for the DMSO-treated control. Despite having identified KIN1400 and KIN1000 in similar screens that selected for small molecules that activate RLR-dependent signaling, the two compounds induced innate immune gene expression but little expression of type I and III IFNs, suggesting that they induce transcriptional activity that is distinct from that induced by IFN treatment alone and also different from that induced by RLR agonist RNA, which potently induces type I IFN expression (12,13). KIN1400 suppresses WNV in cultured cells.…”
Section: Kin1400 Triggers Irf3-dependent Innate Immune Antiviral Genementioning
confidence: 99%
“…These products act in concert to suppress and control virus infection. Synthetic and natural ligands that artificially induce PRR signaling and activate the innate immune response in cells and in mice show a proof of concept that triggering PRR pathways for innate immune induction can provide protection against virus infection (13,14). Signaling convergence to activate IRF3 is a common theme shared among PRRs (12).…”
mentioning
confidence: 99%